1996
DOI: 10.1002/(sici)1096-8644(199609)101:1<55::aid-ajpa5>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Climbing, brachiation, and terrestrial quadrupedalism: Historical precursors of hominid bipedalism

Abstract: The vertical-climbing account of the evolution of locomotor behavior and morphology in hominid ancestry is reexamined in light of recent behavioral, anatomical, and paleontological findings and a more firmly established phylogeny for the living apes. The behavioral record shows that African apes, when arboreal, are good vertical climbers, and that locomotion during traveling best separates the living apes into brachiators (gibbons), scrambling/ climbing/brachiators (orangutans), and terrestrial quadrupeds (gor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
219
2
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(231 citation statements)
references
References 206 publications
(303 reference statements)
8
219
2
2
Order By: Relevance
“…The focus has shifted instead to whether bipedalism was preceded by exclusively or nearly exclusively climbing and suspensory behaviors (Tuttle, 1969aStern, 1975), including vertical climbing (Prost, 1980;Fleagle et al, 1981;Stern and Susman, 1981;Ishida et al, 1985;Senut, 1988), in a large-bodied ape, or whether the ancestral condition included a significant terrestrial (Gebo, 1996;Sarmiento, 1998), possibly knuckle-walking component (Washburn, 1967;Corruccini, 1978;Shea and Inouye, 1993;Begun, 1993aBegun, , 1994Strait, 2000, 2001d). Arguments for suspensory/ climbing ancestors ( Fig.…”
Section: A Century Of Modelsmentioning
confidence: 98%
See 1 more Smart Citation
“…The focus has shifted instead to whether bipedalism was preceded by exclusively or nearly exclusively climbing and suspensory behaviors (Tuttle, 1969aStern, 1975), including vertical climbing (Prost, 1980;Fleagle et al, 1981;Stern and Susman, 1981;Ishida et al, 1985;Senut, 1988), in a large-bodied ape, or whether the ancestral condition included a significant terrestrial (Gebo, 1996;Sarmiento, 1998), possibly knuckle-walking component (Washburn, 1967;Corruccini, 1978;Shea and Inouye, 1993;Begun, 1993aBegun, , 1994Strait, 2000, 2001d). Arguments for suspensory/ climbing ancestors ( Fig.…”
Section: A Century Of Modelsmentioning
confidence: 98%
“…1), on the other hand, cite numerous terrestrial traits shared between hominins and African apes to the exclusion of Asian apes (Sarmiento, 1994(Sarmiento, , 1988Gebo, 1992Gebo, , 1996. A few researchers have suggested that palmigrade terrestriality preceded bipedalism (Delmas, 1972;Hotton et al, 1984).…”
Section: A Century Of Modelsmentioning
confidence: 99%
“…41 This close-packing mechanism in the African apes may be aided by the near 100% occurrence of early fusion of the os centrale to the scaphoid in Pan and Gorilla (a characteristic shared with hominins). 42,[44][45][46][47][48][49][50][51] The os centrale portion of the scaphoid forms a broad, stable articular surface for the trapezium and trapezoid. In wrist extension, the os centrale becomes lodged within an embrasure formed by the capitate head and the trapezoid, 42,44,50 and scaphoid-centrale fusion might provide increased resistance to extension moments at the midcarpal joint.…”
Section: Osteology and Knuckle Walkingmentioning
confidence: 99%
“…Although early hominins were not chimpanzees per se, some researchers have argued that the last common ancestor of humans and chimpanzees was probably quite chimpanzee-like (20), including in its locomotion (21,22). Furthermore, when the prospects of climbing in hominins are discussed in the paleoanthropological literature, the model that is used is often a chimpanzee one (e.g., refs.…”
mentioning
confidence: 99%